Humane killer eaudiobook - Gabaldon, Diana (Recorded Books Inc., 2016)
Diana Gabaldon teams with her son, fantasy author Sam Sykes, for this exclusive audio fantasy short from Recorded Books. Sorry Outlander fans, no highlanders or time travelers in this story, but there is a pot-smoking zombie.